Apamin from bee venom suppresses inflammation in a murine model of gouty arthritis. (15th July 2020) - Lee, Yun Mi; Cho, Soo-Na; Son, Eunjung; Song, Chang-Hwa; Kim, Dong-Seon
Abstract: Ethnopharmacological relevance: Bee venom (BV) has been used for the treatment of inflammatory diseases, such as rheumatoid arthritis, and for the relief of pain in traditional oriental medicine. Aim of study: The aim of this study was to determine the anti-inflammatory effect of BV on monosodium urate (MSU)-induced gouty arthritis in a mouse model. Materials and methods: To develop a mouse model of acute gouty arthritis, 4 mg 50 μL −1 of MSU crystal suspension was injected intradermally into the right paw. After MSU crystal injection, we evaluated inflammatory cytokine production in mice of the BV-treated (0.5 and 1 mg kg −1 body weight) and apamin (APM)-treated (0.5 and 1 mg kg −1 body weight) groups. The positive control group was administered a colchicine (1 mg kg −1 body weight) injection with MSU crystals. Results: BV and APM treatment suppressed inflammatory paw edema in MSU-administered mice. It also exerted anti-inflammatory effects in mice with gouty arthritis by inhibiting proinflammatory cytokine production and inflammasome formation. Interestingly, MSU crystal formation was decreased by BV and APM treatment. Conclusions: These results suggest that the APM from BV might be useful for the treatment of gouty arthritis due to its anti-inflammatory activities. Graphical abstract: Image 1